Sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof

By co-doping with Ti, K, and Al and coating with organic and inorganic carbon sources, the crystal structure and conductivity of the sodium iron pyrophosphate positive electrode material are optimized, the conductivity and density problems of the existing materials are solved, and a sodium iron pyrophosphate positive electrode material with high compaction density and high gram capacity is achieved.

CN120727795APending Publication Date: 2025-09-30SHANGHAI PUNA ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510907858.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

The existing sodium iron pyrophosphate positive electrode material has poor electronic conductivity, low ionic conductivity, and low compaction density, making it difficult to apply commercially.

Method used

Ti, K, and Al co-doped sodium iron pyrophosphate positive electrode material is used, and a three-dimensional conductive network is formed by coating with organic and inorganic carbon sources. The crystal structure and conductivity of the material are optimized by precisely controlling the proportion of each element and process parameters.

Benefits of technology

It improves the ionic conductivity and electronic conductivity of the material, increases the specific capacity and true density, enhances the compaction density of the material, and promotes the utilization of the material capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120727795A_ABST
    Figure CN120727795A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium ferric phosphate pyrophosphate positive electrode material as well as a preparation method and application thereof, belongs to the technical field of sodium ion batteries, and solves the problems of complex preparation method, low compaction density and relatively low gram volume in the preparation process of sodium ferric phosphate pyrophosphate in the prior art. The ferric sodium pyrophosphate positive electrode material comprises a base material and a coating layer coating the surface of the base material, the molecular formula of the matrix material is Na (4-x) Fe (3-y) Mz (PO4) 2P2O7Na; wherein M comprises Ti, K and Al, N is F, the value range of x is larger than 0 and smaller than or equal to 0.02, the value range of y is larger than 0 and smaller than or equal to 0.1, the value range of z is larger than 0 and smaller than or equal to 0.025, the value range of a is larger than 0 and smaller than or equal to 0.01, and the coating layer is a carbon material. The sodium ferric pyrophosphate positive electrode material disclosed by the invention is high in compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a high compaction density sodium iron phosphate pyrophosphate positive electrode material, a preparation method thereof, and applications thereof. Background Art

[0002] At present, the sodium-ion battery system has good application prospects. In sodium-ion batteries, the design of positive electrode materials is very important. At present, the common positive electrode materials for sodium-ion batteries mainly include iron-based materials represented by sodium ferrous pyrophosphate (abbreviated as NFPP). However, the existing NFPP has poor electronic conductivity and low ionic conductivity, resulting in low gram capacity. At the same time, the low compaction density makes NFPP difficult to commercialize. Therefore, how to improve the gram capacity and compaction density of NFPP has become an urgent problem to be solved. Summary of the Invention

[0003] In view of the above analysis, the embodiments of the present invention aim to provide a high compaction density sodium iron pyrophosphate positive electrode material and its preparation method and application, so as to solve at least one of the following problems: the preparation process of sodium iron pyrophosphate in the prior art is complicated, the compaction density is low, and the gram capacity is relatively low.

[0004] The present invention provides a sodium iron phosphate pyrophosphate positive electrode material, which includes a base material and a coating layer coated on the surface of the base material; the molecular formula of the base material is Na 4-x Fe 3-y M z (PO4)2P2O7N a ; Among them, M includes Ti, K and Al, N is F, the value range of x is: 0<x≤0.02, the value range of y is: 0<y≤0.1, the value range of z is: 0<z≤0.025, the value range of a is: 0<a≤0.01, and the coating layer is carbon material.

[0005] Furthermore, the mass fraction of the coating layer is 1% to 2%.

[0006] Furthermore, the material sources of the coating layer include organic carbon sources and inorganic carbon sources.

[0007] Furthermore, the mass ratio of the organic carbon source to the inorganic carbon source is 9 to 12:1.

[0008] Furthermore, the organic carbon source is glucose, and the inorganic carbon source is carbon nanotubes.

[0009] The present invention also provides a method for preparing the above-mentioned sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0010] S1. Mixing and grinding a sodium source, an iron source, a phosphorus source, a titanium source, a potassium source, an aluminum source, a fluorine source, and glucose, and then adding carbon nanotubes and stirring to prepare a slurry;

[0011] S2, spray drying the slurry to obtain spherical dry powder;

[0012] S3, crushing the dry powder and mixing it according to the size of the particles to obtain a mixture;

[0013] S4, sintering the mixed material to obtain a sintered material;

[0014] S5. The sintered material is crushed to obtain a sodium iron pyrophosphate positive electrode material.

[0015] Furthermore, in S1, the molar ratio of sodium, iron, phosphorus, titanium, potassium, aluminum and fluorine elements is controlled to be Na:Fe:P:Ti:K:Al:F=3.98~4:2.9~3:4:0.001~0.01:0.001~0.01:0.001~0.01:0.001~0.01.

[0016] Furthermore, the sodium source and the phosphorus source include at least one of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; and the iron source includes at least one of ferric phosphate and ferric oxide.

[0017] Furthermore, in S4, the sintering holding temperature is 500-600°C.

[0018] The present invention also discloses a sodium ion battery, which comprises the above-mentioned positive electrode material.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0020] The sodium ferric phosphate pyrophosphate positive electrode material of the present invention is co-doped with Ti, K, and Al to reduce crystal volume and expand sodium ion transmission channels. The synergistic effect of the three elements can stabilize the crystal structure of the material. After F ion doping, vacancies and defects in the crystal are increased, which is beneficial to improving the intrinsic conductivity of the material. The co-doping with Ti, K, Al, and F, and the precise control of the ratio of each element, can improve the material's ionic conductivity while optimizing the material's crystal structure, which is beneficial to improving the material's specific capacity and true density.

[0021] The sodium iron phosphate pyrophosphate positive electrode material of the present invention adopts a combination of organic carbon source and inorganic carbon source coating to form a three-dimensional conductive network, which can help improve the electronic conductivity of the material and promote the use of the material capacity; the material sources of the coating layer of the sodium iron phosphate pyrophosphate positive electrode material of the present invention include organic carbon source and inorganic carbon source, and by precisely controlling the quality of the organic carbon source and the inorganic carbon source, the amorphous carbon material generated after the organic carbon is pyrolyzed is cross-linked with the carbon nanotubes and attached to the base material to form a three-dimensional conductive network, which can help improve the electronic conductivity of the material and promote the use of the material capacity.

[0022] In the preparation method of the sodium iron phosphate pyrophosphate positive electrode material of the present invention, the types of raw materials are precisely controlled, so that the introduction of raw materials that are easy to produce gas during the synthesis process can be reduced, so that the sodium iron phosphate pyrophosphate material has a lower porosity and thus a higher density, which is beneficial to improving the compaction density of the material.

[0023] In the preparation method of the sodium iron phosphate pyrophosphate positive electrode material of the present invention, by controlling the optimization of materials, combining the control of process parameters of each step and particle grading, it is ensured that the obtained sodium iron phosphate pyrophosphate material has a higher compaction density and a higher gram capacity.

[0024] The sodium ion battery of the present invention includes a sodium iron phosphate pyrophosphate positive electrode material with a high compaction density. The beneficial effects of the sodium ion battery are brought about by the sodium iron phosphate pyrophosphate positive electrode material with a high compaction density, which will not be described in detail.

[0025] In the present invention, the above-mentioned technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of the present invention will be described in the following description, and some advantages will become apparent from the description or be learned through practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like parts throughout the drawings.

[0027] Figure 1 This is the XRD pattern of the high compaction density sodium iron pyrophosphate positive electrode material of Example 1;

[0028] Figure 2 This is the charge and discharge curve of the button battery assembled in Example 1. DETAILED DESCRIPTION

[0029] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0030] The present invention provides a sodium iron phosphate pyrophosphate positive electrode material, which includes a base material and a coating layer coated on the surface of the base material; the molecular formula of the base material is Na 4-x Fe 3-y M z (PO4)2P2O7N a ; Wherein, M includes Ti, K and Al, N is F; the value range of x is: 0<x≤0.02, the value range of y is: 0<y≤0.1, the value range of z is: 0<z≤0.025, the value range of a is: 0<a≤0.01, and the coating layer is carbon material.

[0031] For example, the molecular formula of the matrix material is Na4Fe 2.9 Ti 0.003 K 0.003 Al 0.004 P4O 15 F 0.005 、Na4Fe 2.9 Ti 0.0 1K 0.003 Al 0.005 P4O 15 F 0.002 、Na4Fe 2.92 Ti 0.01 K 0.005 Al 0.01 P4O 15 F 0.005 、Na 3.98 Fe 2.95 Ti 0.003 K 0.01 Al 0.005 P4O 15 F 0.01 .

[0032] Specifically, considering that too much coating layer will result in a low compaction density, while too little coating layer will result in poor conductivity and affect the material's specific capacity, the coating layer's mass fraction is controlled to be 1% to 2%, for example, 2%, 1.8%, 1.5%, 1.3%, or 1%.

[0033] Specifically, the material sources of the coating layer include organic carbon sources and inorganic carbon sources.

[0034] Preferably, the organic carbon source is glucose and the inorganic carbon source is carbon nanotubes.

[0035] It should be noted that after the pyrolysis of organic carbon, the amorphous carbon material is cross-linked with the carbon nanotubes and attached to the matrix material to form a three-dimensional conductive network, which can help improve the electronic conductivity of the material and promote the use of the material capacity.

[0036] Specifically, the total mass percentage of the organic carbon source and the inorganic carbon source to the total mass percentage of the raw materials is controlled to be 2.8-3.3%, for example, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, or 3.3%.

[0037] Specifically, considering that too much organic carbon source will produce a large amount of amorphous carbon, resulting in a decrease in the material's conductivity, while too little will not achieve the desired coating effect, the mass ratio of the organic carbon source to the inorganic carbon source is controlled to be 9 to 12:1, for example, 9:1, 10:1, 11:1, or 12:1.

[0038] Compared with the prior art, the sodium iron phosphate pyrophosphate positive electrode material of the present invention is co-doped with Ti, K, and Al to reduce the crystal volume and expand the sodium ion transmission channel. At the same time, the synergistic effect of the three can stabilize the crystal structure of the material. After F ion doping, the vacancies and defects in the crystal increase, which is beneficial to improving the intrinsic conductivity of the material. The use of Ti, K, Al and F for co-doping can improve the ionic conductivity of the material while optimizing the crystal structure of the material, which is beneficial to improving the specific capacity and true density of the material. The combination of organic carbon source and inorganic carbon source coating forms a three-dimensional conductive network, which can be beneficial to improving the electronic conductivity of the material and promoting the use of the material capacity.

[0039] Specifically, the space group of the crystal structure of the sodium iron pyrophosphate positive electrode material is Pn21a.

[0040] The present invention discloses a method for preparing the above-mentioned sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0041] S1. Mixing and grinding a sodium source, an iron source, a phosphorus source, a titanium source, a potassium source, an aluminum source, a fluorine source, and glucose, and then adding carbon nanotubes and stirring to prepare a slurry;

[0042] S2, spray drying the slurry to obtain spherical dry powder;

[0043] S3, crushing the dry powder and mixing it according to the size of the particles to obtain a mixture;

[0044] S4, sintering the mixed material to obtain a sintered material;

[0045] S5. The sintered material is crushed to obtain a sodium iron pyrophosphate positive electrode material.

[0046] Specifically, in the above S1, considering that too high a titanium content is prone to generating impurities, while too low a content cannot stabilize the lattice structure; too high a potassium content can distort or block the channels for sodium ion insertion / extraction, while too low a content cannot expand the sodium ion transmission channels; too high an aluminum content can destroy the crystal structure and generate impurities, while too low a content cannot stabilize the crystal structure and improve ionic conductivity; too high a fluorine content can destroy the crystal structure, while too low a content cannot effectively fill the lattice gaps and stabilize the PO bond structure. Therefore, the molar ratio of sodium, iron, phosphorus, titanium, potassium, aluminum, and fluorine is controlled to be Na:Fe:P:Ti:K:Al:F=3.98~4:2.9~3:4:0.001~0.01:0.001~0.01:0.001~0.01:0.001~0.01:0.001~0.01.

[0047] Specifically, in S1 above, the sodium source and phosphorus source include at least one of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; and the iron source includes at least one of ferric phosphate and ferric oxide. It should be noted that the use of the above raw materials can reduce the introduction of raw materials that are prone to gas production during the synthesis process, resulting in the sodium iron pyrophosphate material having a lower porosity and thus a higher density, which is beneficial for improving the compaction density of the material.

[0048] Specifically, in the above S1, the titanium source includes at least one of titanium dioxide and tetrabutyl titanate; the potassium source includes at least one of potassium oxide, potassium phosphate, and potassium hydroxide; the aluminum source includes at least one of aluminum oxide, aluminum phosphate, and aluminum hydroxide; and the fluorine source includes at least one of sodium fluoride and ammonium fluoride.

[0049] Specifically, in the above S1, adding glucose first and then adding carbon nanotubes is beneficial to improving the material grinding efficiency and controlling the grinding particle size.

[0050] Specifically, in the above S1, the D50 of the material obtained by grinding is between 350 and 400 nm, and the D90 is less than 1 micron.

[0051] Specifically, in the above S2, considering that the inlet air temperature of the spray dryer is too high, it is easy to cause segregation, and too low a temperature reduces the efficiency; too high an outlet air temperature reduces the efficiency, and too low a temperature does not dry the material thoroughly. Therefore, the inlet air temperature of the spray dryer is controlled at 160-180°C (for example, 160°C, 170°C, 180°C), and the outlet air temperature is controlled at 95-110°C (for example, 95°C, 100°C, 110°C); the feed rate is 290-300 mL / min (for example, 290 mL / min, 295 mL / min, 300 mL / min), and the atomizer speed is 23000-24000 r / min (for example, 23000 r / min, 23500 r / min, 24000 r / min).

[0052] Specifically, in the above S3, during mixing, the average particle size of the large particles is 3.5 to 4 microns, and the average particle size of the small particles is 0.4 to 0.6 microns; mixing large particles and small particles can achieve the effect of particle grading. Considering that during mixing, too much or too little mass ratio of large particles cannot achieve the purpose of particle mixing, the mass proportion of large particles is controlled to be 50% to 85% of the total mass, for example, 50%, 60%, 70%, 80%, and 85%.

[0053] Specifically, in the above S4, the specific steps of sintering are:

[0054] In a tubular furnace, the gas atmosphere is controlled to be nitrogen, the holding temperature is 500-600° C., and the holding time is 6-10 hours; and the sintered material is obtained by naturally cooling to room temperature.

[0055] During the sintering process, considering that if the temperature is too high and the holding time is too long, it is easy to produce impurities of sodium ferric pyrophosphate, and if the temperature is too low and the holding time is too short, the material crystal growth is incomplete. Therefore, the holding temperature is controlled to be 500-600℃, for example, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃; the holding time is 6-10h, for example, 6h, 7h, 8h, 9h, 10h.

[0056] Specifically, the preparation method further includes crushing the sintered material to an average particle size of 1 to 2 microns to obtain a high energy density sodium iron pyrophosphate positive electrode material.

[0057] The sodium iron phosphate pyrophosphate positive electrode material of the present invention has a high compaction density. For example, the compaction density is 2.41 g / cm 3 Above, for example 2.41 to 2.5 g / cm 3 The button cell assembled with the sodium iron phosphate pyrophosphate cathode material of the present invention has a 0.3C charge gram capacity of 116 mAh / g or more, such as 116.2 to 120 mAh / g, and a 0.33C discharge gram capacity of 106 mAh / g or more, such as 106.1 to 111 mAh / g.

[0058] The present invention also provides an application of the above-mentioned sodium iron phosphate pyrophosphate positive electrode material, and the above-mentioned sodium iron phosphate pyrophosphate positive electrode material can be used in sodium ion batteries.

[0059] The present invention also discloses a sodium ion battery, which includes the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0060] Example 1

[0061] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the preparation method comprising:

[0062] Sodium phosphate, ferric phosphate, titanium dioxide, aluminum oxide, potassium oxide, ferric oxide, and sodium fluoride were weighed according to a stoichiometric molar ratio of Na:Fe:P:Ti:K:Al:F=4:2.9:4:0.003:0.003:0.004:0.005, and 2.9% glucose was added for grinding. The particle size D50 was controlled between 350 and 400 nm and D90 was less than 1 micron. Then, 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 175°C and an outlet air temperature of 105°C, with a feed rate of 300 mL / min and an atomizer speed of 24,000 r / min to obtain spherical dry powder. After the dry powder was crushed, it was mixed according to large and small particles, wherein the average particle size of the large particles was 4 microns, the average particle size of the small particles was 0.6 microns, and the mass proportion of the large particles was 80%. The spray material after optimal grading is sintered in a nitrogen atmosphere: the temperature is kept at 500°C for 8 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material; the sintered material is crushed to an average particle size of about 1.5 microns to obtain a sodium iron phosphate pyrophosphate positive electrode material with high energy density.

[0063] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this embodiment is Na4Fe 2.9 Ti 0.003 K 0.003 Al 0.004 P4O 15 F 0.005 .

[0064] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this embodiment are shown in Table 1 below. The XRD pattern of the sodium iron phosphate pyrophosphate positive electrode material is shown in Table 1 below. Figure 1 shown.

[0065] The above-mentioned sodium iron phosphate pyrophosphate positive electrode material was used as the positive electrode, the sodium sheet was used as the negative electrode, the electrolyte was 1 mol / L NaClO4 (EC:DEC=1:1+5% FEC), and a CR2032 button battery was assembled to test the battery performance. Figure 2 The charge and discharge curves of the button cell battery assembled in Example 1 are shown in Table 1.

[0066] Example 2

[0067] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the preparation method comprising:

[0068] Sodium phosphate, ferric phosphate, titanium dioxide, aluminum oxide, potassium oxide, ferric oxide, and sodium fluoride were weighed according to a stoichiometric molar ratio of Na:Fe:P:Ti:K:Al:F=4:2.9:4:0.01:0.003:0.005:0.002, and 2.9% glucose was added for grinding. The particle size D50 was controlled between 360 and 400 nm and D90 was less than 1 micron. Then 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 165°C and an outlet air temperature of 100°C, with a feed rate of 290 mL / min and an atomizer speed of 24,000 r / min to obtain spherical dry powder. After the dry powder was crushed, it was mixed according to large and small particles, wherein the average particle size of the large particles was 3.5 microns, the average particle size of the small particles was 0.4 meters, and the mass proportion of the large particles was 85%. The spray material after the preferred grading is sintered in a nitrogen atmosphere: the temperature is kept at 530° C. for 8 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material; the sintered material is crushed to an average particle size of about 2 microns to obtain a sodium iron phosphate pyrophosphate positive electrode material with high energy density.

[0069] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this embodiment is Na4Fe 2.9 Ti 0.01 K 0.003 Al 0.005 P4O 15 F 0.002 .

[0070] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this example are shown in Table 1 below.

[0071] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0072] Example 3

[0073] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the preparation method comprising:

[0074] Sodium pyrophosphate, ferric phosphate, titanium dioxide, aluminum oxide, potassium oxide, ferric oxide, and sodium fluoride were weighed according to a stoichiometric ratio of Na:Fe:P:Ti:K:Al:F=4:2.92:4:0.01:0.005:0.01:0.005, and 2.9% glucose was added for grinding. The particle size D50 was controlled to be between 350 and 390 nm and D90 <1 micron. Then, 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 170°C and an outlet air temperature of 100°C, with a feed rate of 300 mL / min and an atomizer speed of 24,000 r / min to obtain spherical dry powder. After the dry powder was crushed, it was mixed according to large and small particles, wherein the average particle size of the large particles was 3.7 microns, the average particle size of the small particles was 0.5 microns, and the mass proportion of the large particles was 75%. The spray material after optimal grading is sintered in a nitrogen atmosphere: the temperature is kept at 540°C for 6 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material; the sintered material is crushed to an average particle size of about 1 micron to obtain a sodium iron phosphate pyrophosphate positive electrode material with high energy density.

[0075] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this embodiment is Na4Fe 2.92 Ti 0.01 K 0.005 Al 0.01 P4O 15 F 0.005 .

[0076] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this example are shown in Table 1 below.

[0077] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0078] Example 4

[0079] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, the preparation method comprising:

[0080] Sodium phosphate, ferric phosphate, titanium dioxide, aluminum oxide, potassium oxide, ferric oxide, and sodium fluoride were weighed according to a stoichiometric molar ratio of Na:Fe:P:Ti:K:Al:F = 3.98:2.95:4:0.003:0.01:0.005:0.01, and 2.9% glucose was added for grinding. The particle size D50 was controlled between 350 and 400 nm and D90 was less than 1 micron. Then 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 100°C, with a feed rate of 300 mL / min and an atomizer speed of 23,500 r / min to obtain spherical dry powder. After the dry powder was crushed, it was mixed according to large and small particles, wherein the average particle size of the large particles was 3.6 microns, the average particle size of the small particles was 0.45 meters, and the mass proportion of the large particles was 80%. The spray material after optimal grading is sintered in a nitrogen atmosphere: the temperature is kept at 520°C for 7 hours to obtain a sodium iron phosphate pyrophosphate positive electrode material; the sintered material is crushed to an average particle size of about 1.8 microns to obtain a sodium iron phosphate pyrophosphate positive electrode material with high energy density.

[0081] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this embodiment is Na 3.98 Fe 2.95 Ti 0.003 K 0.01 Al 0.005 P4O 15 F 0.01 .

[0082] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this example are shown in Table 1 below.

[0083] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0084] The inventors have conducted extensive research during the research process and now use some solutions with poor performance as comparative examples.

[0085] Comparative Example 1

[0086] Sodium phosphate, ferric phosphate, titanium dioxide, aluminum oxide, potassium oxide, and ferric oxide were weighed according to the stoichiometric ratio of Na:Fe:P:Ti:K:Al = 4:2.9:4:0.003:0.003:0.004, and 2.7% glucose was added for grinding to control the particle size D50 between 350 and 400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 110°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to the particle size, with the average particle size of the large particles being 4 microns and the average particle size of the small particles being 0.6 microns. The mass proportion of the large particles was 70%. The preferably graded spray material was sintered at 500°C in a nitrogen atmosphere for 8 hours to obtain the sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 1.5 microns to obtain the sodium ferric pyrophosphate material.

[0087] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 Ti 0.003 K 0.003 Al 0.004 P4O 15 .

[0088] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0089] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0090] Comparative Example 2

[0091] Sodium phosphate, iron phosphate, titanium dioxide, and ferric oxide were weighed according to the stoichiometric ratio of Na:Fe:P:Ti:K = 4:2.9:4:0.005:0.005, and 2.5% glucose was added for grinding to control the particle size (D50) to between 350-400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 170°C and an outlet air temperature of 100°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to the particle size, with the average particle size of the large particles being 3.5 microns and the average particle size of the small particles being 0.5 microns. The mass proportion of the large particles was 75%. The preferably graded spray material was sintered at 580°C in a nitrogen atmosphere for 8 hours to obtain the sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 1.5 microns to obtain the sodium ferric pyrophosphate material.

[0092] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 Ti 0.005 K 0.005 P4O 15 .

[0093] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0094] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0095] Comparative Example 3

[0096] Sodium carbonate, ferrous oxalate, titanium dioxide, and sodium dihydrogen phosphate were weighed according to a stoichiometric ratio of Na:Fe:P:Ti = 4:2.9:4:0.01. 2.9% glucose was added for grinding to a particle size of 350-400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 100°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to particle size, with the average particle size of large particles being 4 microns and the average particle size of small particles being 0.6 microns. The mass proportion of large particles was 60%. The preferably graded spray material was sintered at 550°C in a nitrogen atmosphere for 8 hours to obtain a sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 1.5 microns to obtain the sodium ferric pyrophosphate material.

[0097] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 Ti 0.01 P4O 15 .

[0098] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0099] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0100] Comparative Example 4

[0101] Sodium carbonate, ferric phosphate, aluminum oxide, and sodium dihydrogen phosphate were weighed according to a stoichiometric ratio of Na:Fe:P:Al = 4:2.9:4:0.01. 2.7% glucose was added for grinding to a particle size of 350-400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 170°C and an outlet air temperature of 100°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to particle size, with the average particle size of large particles being 3.8 microns and the average particle size of small particles being 0.45 microns. The mass proportion of large particles was 55%. The preferably graded spray material was sintered at 530°C for 6 hours in a nitrogen atmosphere to obtain a sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 2 microns to obtain the sodium ferric pyrophosphate material.

[0102] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 Al 0.01 P4O 15 .

[0103] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0104] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0105] Comparative Example 5

[0106] Sodium carbonate, ferric phosphate, potassium oxide, sodium fluoride, and disodium dihydrogen pyrophosphate were weighed according to the stoichiometric ratio of Na:Fe:P:K:F = 4:2.9:4:0.01:0.005, and 2.7% glucose was added for grinding to control the particle size (D50) to between 350-400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 175°C and an outlet air temperature of 105°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to particle size, with the average particle size of large particles being 3.7 microns and the average particle size of small particles being 0.55 microns. The mass proportion of large particles was 75%. The preferably graded spray material was sintered at 550°C in a nitrogen atmosphere for 8 hours to obtain a sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 1.2 microns to obtain the sodium ferric pyrophosphate material.

[0107] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 K 0.01P4O 15 F 0.005 .

[0108] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0109] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0110] Comparative Example 6

[0111] The raw materials of this comparative example are of the same type as those of Example 1, except that:

[0112] The molar ratio is Na:Fe:P:Ti:K:Al:F=4:2.98:4:0.02:0.02:0.03:0.02. The remaining steps are the same as in Example 1 and will not be repeated here.

[0113] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.98 Ti 0.02 K 0.02 Al 0.03 P4O 15 F 0.02 .

[0114] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0115] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0116] Comparative Example 7

[0117] The preparation method of this comparative example is roughly the same as that of Example 1, except that:

[0118] The mass proportion of large particles is 45%, the sintering temperature is 480° C., and the remaining steps are the same as those in Example 1 and will not be repeated here.

[0119] The compaction density results of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example are shown in Table 1 below.

[0120] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0121] Comparative Example 8

[0122] Sodium carbonate, ferric phosphate, and sodium dihydrogen phosphate were weighed according to a stoichiometric molar ratio of Na:Fe:P = 4:2.9:4. 2.7% glucose was added for grinding to a particle size between 350-400 nm. 0.25% carbon nanotubes were added and stirred for 1 hour. The prepared slurry was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 110°C to obtain a spherical dry powder. After the spray material was crushed, it was mixed according to particle size, with the average particle size of large particles being 4 microns and the average particle size of small particles being 0.6 microns. The mass proportion of large particles was 70%. The preferably graded spray material was sintered at 500°C for 8 hours in a nitrogen atmosphere to obtain a sodium ferric pyrophosphate positive electrode material. The sintered material was crushed to an average particle size of 1.5 microns to obtain the sodium ferric pyrophosphate material.

[0123] The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material obtained in this comparative example is Na4Fe 2.9 P4O 15 .

[0124] The above-mentioned sodium ferric phosphate pyrophosphate cathode material was used as the positive electrode, the sodium sheet as the negative electrode, and the electrolyte was 1 mol / L NaClO4 (EC:DEC = 1:1 + 5% FEC). A CR2032 button-type battery was assembled and the battery performance was tested. The results are shown in Table 1.

[0125] Table 1 Performance data

[0126]

[0127]

[0128] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.

Claims

1. A sodium iron pyrophosphate positive electrode material, characterized in that The sodium iron phosphate pyrophosphate positive electrode material comprises a base material and a coating layer coated on the surface of the base material; the molecular formula of the base material is Na 4-x Fe 3-y M z (PO4)2P2O7N a ; Wherein, M includes Ti, K and Al, N is F, the value range of x is: 0<x≤0.02, the value range of y is: 0<y≤0.1, the value range of z is: 0<z≤0.025, the value range of a is: 0<a≤0.01, and the coating layer is a carbon material.

2. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The mass fraction of the coating layer is 1% to 2%.

3. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The material sources of the coating layer include organic carbon sources and inorganic carbon sources.

4. The sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that The mass ratio of the organic carbon source to the inorganic carbon source is 9 to 12:

1.

5. The sodium iron phosphate pyrophosphate positive electrode material according to claim 3 or 4, characterized in that The organic carbon source is glucose, and the inorganic carbon source is carbon nanotubes.

6. A method for preparing the sodium iron pyrophosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mixing and grinding a sodium source, an iron source, a phosphorus source, a titanium source, a potassium source, an aluminum source, a fluorine source, and glucose, and then adding carbon nanotubes and stirring to prepare a slurry; S2, spray drying the slurry to obtain spherical dry powder; S3, crushing the dry powder and mixing it according to the size of the particles to obtain a mixture; S4, sintering the mixed material to obtain a sintered material; S5. The sintered material is crushed to obtain a sodium iron pyrophosphate positive electrode material.

7. The preparation method according to claim 6, characterized in that In the S1, the molar ratio of sodium, iron, phosphorus, titanium, potassium, aluminum and fluorine is controlled to be Na:Fe:P:Ti:K:Al:F=3.98~4:2.9~3:4:0.001~0.01:0.001~0.01:0.001~0.01:0.001~0.

01.

8. The preparation method according to claim 6, characterized in that The sodium source and phosphorus source include at least one of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; the iron source includes at least one of ferric phosphate and ferric oxide.

9. The preparation method according to any one of claims 6 to 8, characterized in that In the step S4, the sintering holding temperature is 500-600°C.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 5 or the sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN121366889A